HEMATOPOIETIC STUDY OF THE METHANOLIC ROOT EXTRACT OF BETA VULGARIS ON ALBINO RATS-AN IN VIVO STUDY - INDHUMATHI.T; KANNIKAPARAMESWARI.K (International Journal of Pharma and Bio Sciences, 2012)
Medicines play an important role in human health cure. The plant kingdom constitutes a source of new chemical compounds which may important owing to their potential use in medicine and other applications. The present study investigates the hematopoietic activity of Beta vulgaris in experimental rat models treated with various concentrations of the methanolic extract of the root of Beta vulgaris. Rats were divided into four groups of five each and the groups were as follows: Group 1- Control group; Group 2- Rats were received 100 mg/kg b.w. Beta vulgaris methanolic extract orally for sixteen days; Group 3- Rats were received 200 mg/kg Beta vulgaris methanolic extract orally for sixteen days; Group 4- Rats were received 400mg/kg Beta vulgaris methanolic extract orally for sixteen days. All the groups were given Beta vulgaris extract for sixteen days at 24 hour interval. From the Phytochemical studies it was proved that powdered root of Beta vulgaris contains alkaloids, flavonoids, phenols etc., In this study rats treated with methanolic root extract of Beta vulgaris recorded significant increase s in Packed Cell Volume (PCV), Hemoglobin concentration, Red Blood Cell counts (RBCs), and Total lymphocyte count .The other parameters such as MCV, MCH, MCHC also showed a dose dependent fashion.